(untitled) (Eurasian Research Bulletin, 2024)
In this article, as a result of studying foreign experience in the development of the institute of tax consulting, the issues of improving the legal framework for the activities of tax consultants in our country, as well as theoretical and organizational forms of tax consulting, legal organization and importance in the development of the tax consulting system were studied. economics has been deeply studied. Also in mamlkatim, on the basis of accurate data, the trend of development of the institute of tax consulting is analyzed, in what state it is today.